Plasma parameters evolution during conditioning RF discharges in Uragan-2M torsatron - Skibenko, A.I.; Prokopenko, A.V.; Berezhnyj, V.L.; Burchenko, P.Ya.; Krasnyj, V.V.; Kulaga, A.E.; Lesnyakov, G.G.; Lozin, A.V.; Moiseenko, V.E.; Ocheretenko, V.L.; Pavlichenko, O.S.; Pinos, I.B.; et al. (Вопросы атомной науки и техники, 2009)
The results of the plasma parameters optimization measured via two-chord interferometry, radiometry, and the registering of the Нα, CIII, OII lines intensity are discussed. The optimization was realized by variation of RF scenario of the RF power introduction, pressure and magnetic field. Обговорюються результати оптимізації параметрів плазми вимірюваних за допомогою двохордової інтерферометрії, радіометрії і реєстрації інтенсивності ліній Нα, СІІІ, ОІІ. Оптимізація здійснювалась шляхом зміни сценаріїв вводу ВЧ-потужності, тиску і магнітного поля. Обсуждаются результаты оптимизации параметров плазмы, измеряемых с помощью двуххордовой интерферометрии, радиометрии и регистрации интенсивности линий Нα, СІІІ, ОІІ. Оптимизация осуществлялась путем варьирования сценариев ввода ВЧ- мощности, давления и магнитного поля.